Higher carotid-radial pulse wave velocity is associated with non-melancholic depressive symptoms in men - findings from Helsinki Birth Cohort Study - Eriksson Mia D.; Eriksson Johan G.; Kautiainen Hannu; Salonen Minna K.; Mikkola Tuija M.; Kajantie Eero; Wasenius Niko; von Bonsdorff Mikaela; Korhonen Päivi; Laine Merja K. (TAYLOR & FRANCIS LTD, 2022)
Background
Depression and cardiovascular disease (CVD) are major causes of global disease burden that are interrelated through mostly unknown mechanisms. We studied the relationship of melancholic and non-melancholic depressive symptoms with arterial stiffness, an important underlying mechanism of CVD.
Methods
The Helsinki Birth Cohort Study recruited 683 previously extensively phenotyped subjects for this sub-study. Cross-sectional data along with responses regarding depressive symptoms were obtained for each participant. For evaluation of depressive symptoms, the Beck Depression Inventory (BDI)and subscales were used to measure melancholic and non-melancholic depressive symptoms. Arterial stiffness was assessed as pulse wave velocity (PWV) that was measured between the carotid and radial artery, and carotid and femoral artery.
Results
Of the participants, 532 scored <10 on the BDI and were classified as not having depressive symptoms. Of the 151 participants that scored >= 10 on the BDI, 122 were classified as having non-melancholic depressive symptoms and 29 as having melancholic depressive symptoms. Men had higher carotid-radial PWV (crPWV) values than women (p < .001). A positive relationship between BDI scores and crPWV (p < .001) was found in men. We also found higher crPWV in men with non-melancholic depressive symptoms compared to all others. No such differences were found in women.
Discussion
Arterial stiffness has a relationship with depressive symptoms and subtypes of depressive symptoms, at least in men. There is a significant relationship between higher PWV and non-melancholic depressive symptoms in men. Due to the intricate nature of the disease causality or directionality is impossible to infer solely based on this study. Further studies into the subtypes of depressive symptoms may be of benefit to understanding depression.
KEY MESSAGES
It is known that arterial stiffness contributes to cardiovascular disease, and is associated with depression.
Higher Beck Depression Inventory scores are associated with higher carotid-radial pulse wave velocity in men.
Non-melancholic depressive symptoms are associated with higher carotid-radial pulse wave velocity in men.